On the genus Limnocassis Spaeth, with description of two new species from South Africa (Coleoptera: Chrysomelidae: Cassidinae) - Borowiec, Lech; Sekerka, Lukáš (Zootaxa, 2015)
Limnocassis compacta sp. nov. and L. regularis sp. nov. are described from South Africa. They are well distinguished from Limnocassis pumilio (Boheman, 1854), the only known species in the genus, in fine and mostly regular elytral punctation. Colour photographs of all species and new distribution data for L. pumilio are given.